Interdiffusion coefficient and atomic mobility for fcc Ag-Cu-Mg phase at 1073 K (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this work, the interdiffusion coefficient and atomic mobility for fcc Ag-Cu-Mg phase at 1073 K have been investigated by combining diffusion couple experiments and calculations. Based on the experimental composition profiles, the diffusion coefficients at intersection points in diffusion paths were calculated by means of Matano-Kirkaldy method. Using the thermodynamic descriptions available in literature, the atomic mobilities for fcc Ag-Cu-Mg phase were automatically optimized by numerical inverse method incorporated in the CALTPP (CALculation of ThermoPhysical Properties) program. Moreover, the obtained atomic mobilities were verified to be reliable through good agreements between the model-simulated composition profiles and the measured ones. In addition, three-dimensional surfaces for the interdiffusion coefficient, activation energy, and frequency factor were presented. The presently obtained atomic mobilities can be incorporated into the diffusion database for Ag-based alloys, which can contribute to microstructure simulation and materials design.
Keywords: fcc Ag-Cu-Mg; Interdiffusion coefficient; Atomic mobility; CALTPP; Activation energy; Frequency factor